I'm working on function notation and I'm stuck on the following. Please explain: Let f(x)=x^2+4x and g(x)=3x+2 Expand, Simplify and collect like terms a) g(f(-3)= b) f(g(x))= c) g(f(x))=
Follow Math Help Forum on Facebook and Google+
Originally Posted by wild_flowr69 I'm working on function notation and I'm stuck on the following. Please explain: Let f(x)=x^2+4x and g(x)=3x+2 Expand, Simplify and collect like terms a) g(f(-3)= Since and Originally Posted by wild_flowr69 b) f(g(x))= Thus, Originally Posted by wild_flowr69 c) g(f(x))= You have,
View Tag Cloud